Pneumonia hospitalizations and mortality in children 3 - 24-month-old in Nigeria from 2013 to 2020: Impact of pneumococcal conjugate vaccine ten valent (PHiD-CV-10) - Jalo Iliya; Denis R. Shatima; Beckie N. Tagbo; Adejumoke I. Ayede; Abieyuwa O. Fagbohun; Aliu Rasaq; Sarah Nalban; Isaac W. Elon; Ramatu Mohammed-Nafiu; Patience Ahmed; Oladapo B. Oyewole; Ayobami A. Bakare; et al. (Taylor & Francis Group, 2023)
Pneumococcal conjugate vaccine ten valent (PCV 10) was introduced into Nigeria in three phases. Phase 3 introduction started in August 2016. However, its impact on pneumonia admissions and mortality among vaccinated Nigerian children has not been determined. Data in the period before PCV-10 introduction (3 August 2013-2 August 2016), and after (3 August 2017-2 August 2020) were retrospectively extracted from the medical charts of eligible patients aged 3-24 months with hospitalized radiological pneumonia at the University College Hospital (UCH), Ibadan; National Hospital (NH), Abuja; and Federal Teaching Hospital (FTH), Gombe, allowing for an intervening period of 1 year. Proportions of the patients with hospitalized pneumonia and case fatality rates were determined during both periods. The results were compared using z-test, multiple logistic regression analysis and p < .05 was considered significant. Adjusted pneumonia hospitalization rates between the two periods increased at the NH Abuja (10.7% vs 14.6%); decreased at the UCH, Ibadan (8.7% vs 6.9%); and decreased at the FTH, Gombe (28.5% vs 18.9%). Case fatality rates decreased across all the sites during the post-PCV introduction period: NH Abuja, from 6.6% to 4.4% (p = .106); FTH, Gombe, 11.7% to 7.7% (p = .477); and UCH, Ibadan, 2.0% to 0% (p = .045); but only significant at Ibadan. Overall, proportion of hospitalized pneumonia cases decreased after 3 years of PCV 10 introduction into the National Immunization Programme in Nigeria. The case fatality rate during post-PCV 10 introduction decreased at all the three sites, but this difference was significant at the UCH, Ibadan.